Organization for Defense and Cooperation in the Field of Collective Cyber Security in Europe. / Organización para la defensa y cooperación en el ámbito de la seguridad cibernética colectiva en Europa. - ILSIYAROVICH ABDULLIN, ADEL; DAVLETGILDEEV, RUSTEM SHAMILEVICH; ANDREEVICH KOSTIN, SERGEY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper analyses the activities of the Organization for Security and Cooperation in Europe (OSCE), which, as a result of the transformation of the Conference on Security and Cooperation in Europe (CSCE), has become one of the main elements of the European security architecture. The subject of interest is the international legal cooperation of the participating States in the field of international legal provision of the collective cybersecurity. Since its beginning the twenty-first century has been marked by the rapid development of information and communication technologies (ICT), which significantly accelerated communication processes both at the national and international levels. RESUMEN El documento analiza las actividades de la Organización para la Seguridad y la Cooperación en Europa (OSCE), que, como resultado de la transformación de la Conferencia sobre Seguridad y Cooperación en Europa (CSCE), se ha convertido en uno de los principales elementos de la arquitectura de la seguridad europea. El tema de interés es la cooperación jurídica internacional de los Estados participantes en el ámbito de la disposición jurídica internacional de la ciberseguridad colectiva. Desde sus inicios el siglo XXI ha estado marcado por el rápido desarrollo de las tecnologías de la información y la comunicación (TIC), lo cual aceleró significativamente los procesos de comunicación tanto a nivel nacional como internacional.